2005
DOI: 10.4049/jimmunol.175.6.3475
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Accelerate Macrophage-Mediated Digestion of Apoptotic Cells In Vivo as Well as In Vitro

Abstract: It is generally believed that the clearance of apoptotic cells does not lead to inflammation. In contrast, we previously found that injection of apoptotic cells into the peritoneal cavity induced the expression of an inflammatory chemokine, MIP-2, and infiltration of neutrophils, and that anti-MIP-2 Abs suppressed the infiltration significantly. Because our previous study showed that whole-body x-irradiation caused neutrophil infiltration into the thymus along with T cell apoptosis, we examined the role of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“…In another study MF-mediated digestion of apoptotic thymocytes was accelerated in the presence of neutrophils both in vivo and in vitro suggesting that recruitment of neutrophils to the site of massive apoptosis does not induce inflammation but rather accelerates complete digestion of apoptotic cells (48). In light of our results, neutrophils likely contribute to the disappearance of apoptotic cells by participating actively in the clearance of apoptotic cells.…”
Section: Discussionsupporting
confidence: 60%
“…In another study MF-mediated digestion of apoptotic thymocytes was accelerated in the presence of neutrophils both in vivo and in vitro suggesting that recruitment of neutrophils to the site of massive apoptosis does not induce inflammation but rather accelerates complete digestion of apoptotic cells (48). In light of our results, neutrophils likely contribute to the disappearance of apoptotic cells by participating actively in the clearance of apoptotic cells.…”
Section: Discussionsupporting
confidence: 60%
“…This observation is further evidence that dietary antioxidants likely attenuate the radiation-induced inflammatory state, which results in neutrophil demarginalization (33). For instance, in the thymus, neutrophils are recruited from the periphery after massive TBI-induced lymphoid apoptosis and prior to clearance of the apoptotic cells by macrophages (34,35). Such apoptotic tissue injury initiates an immune response that leads to neutrophil demarginalization and peripheral neutrophilia prior to tissue infiltration.…”
Section: Discussionmentioning
confidence: 76%
“…Because the majority of developing thymocytes will fail positive or negative selection, scavenger cells such as macrophages play an important role in thymopoiesis. 42,43 A recent study showed that mice deficient for neutrophil migration were impaired in their ability to clear apoptotic cells after irradiation. 44 Therefore, it is possible that granulocytes function as scavengers of apoptotic thymocytes in the steady state.…”
Section: Discussionmentioning
confidence: 99%